2014
DOI: 10.1002/mus.24287
|View full text |Cite
|
Sign up to set email alerts
|

Reachable workspace in facioscapulohumeral muscular dystrophy (FSHD) by kinect

Abstract: Introduction A depth-ranging sensor (Kinect) based upper extremity motion analysis system was applied to determine the spectrum of reachable workspace encountered in facioscapulohumeral muscular dystrophy (FSHD). Methods Reachable workspaces were obtained from 22 individuals with FSHD and 24 age- and height-matched healthy controls. To allow comparison, total and quadrant reachable workspace relative surface areas (RSA) were obtained by normalizing the acquired reachable workspace by each individual’s arm le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
67
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 57 publications
(68 citation statements)
references
References 25 publications
1
67
0
Order By: Relevance
“…Recently, researchers have begun to utilize the cost-effective and commercially-available Kinect sensor for medical rehabilitation purposes [3]. This report's investigators had originally developed a novel sensorbased upper extremity reachable workspace assessment tool and outcome measure for use in neuromuscular conditions [17][18][19][20][21]. The foundational concept and framework for utilizing the sensor-based reachable workspace as a global upper extremity functional outcome measure has been previously discussed in published studies [17][18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, researchers have begun to utilize the cost-effective and commercially-available Kinect sensor for medical rehabilitation purposes [3]. This report's investigators had originally developed a novel sensorbased upper extremity reachable workspace assessment tool and outcome measure for use in neuromuscular conditions [17][18][19][20][21]. The foundational concept and framework for utilizing the sensor-based reachable workspace as a global upper extremity functional outcome measure has been previously discussed in published studies [17][18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…This report's investigators had originally developed a novel sensorbased upper extremity reachable workspace assessment tool and outcome measure for use in neuromuscular conditions [17][18][19][20][21]. The foundational concept and framework for utilizing the sensor-based reachable workspace as a global upper extremity functional outcome measure has been previously discussed in published studies [17][18][19][20][21]. However, its use and application in an otherwise healthy population with various musculoskeletal shoulder dysfunctions has not yet been explored.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In total 19 local coordinate systems (LCS), following ISB recommendations [27] for axis orientation, were located in the origins indicated by numbers (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) in Figure 1. Then 33 LCSs origin motions relative to parent LCSs (Table 1) Each of 33 trajectory plots was processed to assess different properties of the shape created by hodograph.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, marker placement (i.e., time consuming and potential source of error [8]) and skin displacement during motion are two recognized problems within the MBS field [9]. 2 of 16 Several studies have previously studied the use of the Kinect V1 as MLS for upper limb evaluation to assess reachable workspace on healthy subjects [10], on patients suffering from fascioscapulohumeral muscular dystrophy [11] and patients with Duchenne muscular dystrophy [12]. Another study compared simple planar motions (shoulder abduction and elbow flexion) and found good correlations with MBS results [4].…”
Section: Introductionmentioning
confidence: 99%